Discovery of a novel class of highly potent inhibitors of the p53–MDM2 interaction by structure-based design starting from a conformational argument. Issue 19 (1st October 2016) - Furet, Pascal; Masuya, Keiichi; Kallen, Joerg; Stachyra-Valat, Thérèse; Ruetz, Stephan; Guagnano, Vito; Holzer, Philipp; Mah, Robert; Stutz, Stefan; Vaupel, Andrea; Chène, Patrick; Jeay, Sébastien; et al.
Graphical abstract: Abstract: The p53–MDM2 interaction is an anticancer drug target under investigation in the clinic. Our compound NVP-CGM097 is one of the small molecule inhibitors of this protein–protein interaction currently evaluated in cancer patients. As part of our effort to identify new classes of p53–MDM2 inhibitors that could lead to additional clinical candidates, we report here the design of highly potent inhibitors having a pyrazolopyrrolidinone core structure. The conception of these new inhibitors originated in a consideration on the MDM2 bound conformation of the dihydroisoquinolinone class of inhibitors to which NVP-CGM097 belongs. This work forms the foundation of the discovery of HDM201, a second generation p53–MDM2 inhibitor that recently entered phase I clinical trial.